Dietary Energy Intake and Presence of Aberrant Crypt Foci Are Associated with Phospholipid, Purine, and Taurine Metabolite Abundances in C57BL/6N Mouse Colon. Issue 20 (21st October 2022) - Chatelaine, Haley A.; Ramazani, Cynthia A.; Spencer, Kyle; Olivo‐Marston, Susan; Bailey, Michael T.; McElroy, Joseph; Hatzakis, Emmanuel; Mathé, Ewy A.; Kopec, Rachel E.
Abstract : Scope: Colon metabolomes associated with high‐fat (H) versus energy‐restricted (E) diets in early colorectal cancer (CRC) models have never been directly compared. The objectives of this study are to elucidate metabolites associated with diet, aberrant crypt foci (ACF), and diet:ACF interaction, using a lifetime murine model. Methods and results: Three‐week‐old mice consumed control (C), E, or H initiation diets for 18 weeks. ACF formation is initiated weeks 16–21 with azoxymethane injections, followed by progression diet crossover (to C, E, or H) through week 60. Colon extracts are analyzed using ultra‐high‐performance liquid chromatography‐high resolution mass spectrometry (UHPLC‐HRMS). Metabolites associated with diet, ACF, or diet:ACF are determined using regression models (FDR‐adjusted p ‐value <0.05). No metabolites are significantly associated with initiation diets, but concentrations of acylcarnitines and phospholipids are associated with C, E, and H progression diets. Purines, taurine, and phospholipids are associated with ACF presence. No significant associations between metabolites and diet:ACF interaction are observed. Conclusions: These results suggest that recent, rather than early‐life, diet is more closely associated with the colon metabolome, particularly lipid metabolism. Results from this study also provide candidate biomarkers of early CRC development and provide support for the importance of early diet on influencing pre‐CRC risk. Abstract : Colon metabolomes were investigated in mice consuming high‐fat (H), energy‐restricted (E), or normocaloric control (C) diets during [initiation], and after [progression] azoxymethane administration to induce abberant crypt foci (ACF) formation. Acylcarnitines and phospholipids were associated with progression diets. Purines, amino acids, phospholipids were associated with ACF. These metabolite profiles highlight how energy intake influences colon metabolism and AC development.